Improving School Climate for Better Quality Educational Management - Syahril Syahril; Hadiyanto Hadiyanto (Journal of Educational and Learning Studies, 2018)
School climate is a situation formed by a relationship between the principal and teachers, teachers and teachers, teachers and staffs, teachers and students or relationships among students that characterizes a school and distinguishes a school from others.  School climate might influence and determine the success of teaching and learning process at schools.  The school climate consists of at least four dimensions, namely dimension of relationship, personal growth/development, system maintenance and change, and dimension of physical environment.  Based on the studies done in several countries, school climate can be a variable influencing other variables, such as learning achievement, behavior and teacher job satisfaction, teacher work motivation, teacher morale, teacher creativity, teacher work performance, and teacher discipline. So, when the school principal wants to improve those practices, he or she has to make better school climate through common stages namely preliminary assessment, feedback, reflection and discussion, intervention, and finally reassessment.